Comparing effectiveness of conservative policy to craniofacial surgery in children with metopic synostosis: protocol for an observational cohort study on clinical outcomes, psychosocial well-being and costs in a Dutch academic hospital - Suzanne Polinder; Erwin Ista; Nicole Erler; Irene Mathijssen; Jolanda Okkerse; K Joosten; Natalja Bannink; Mariët Faasse; Sarah Lisa Versnel; Pauline Tio; Merel van Staalduinen; K Dulfer; et al. (BMJ Open)
Introduction Traditionally, surgical intervention has been the standard treatment for children with metopic synostosis, assuming that it reduces the risk of raised intracranial pressure, thereby preventing vision and cognitive impairment, and also restores the abnormal head shape. However, recent research suggests a sporadic occurrence of raised intracranial pressure in patients with metopic synostosis. In addition, following surgery, an overall tendency to have worse cognitive and behavioral outcomes and more refractive errors compared to healthy peers is observed. Research on conservative (non-surgical) treatment in metopic synostosis is limited and lacks a comparative design. The purpose of this study is to compare the (cost-)effectiveness of conservative and surgical treatment in patients with metopic synostosis.Methods and analysis This is the protocol for an observational cohort study with a duration of 8 years. A total of 450 patients with metopic synostosis will be included. The primary outcome is head growth as a predictor for increased intracranial pressure. Non-inferiority with regard to head growth from 0 to 8 years (yearly difference in SD) is determined using a linear mixed model adjusted for potential confounders. Secondary outcomes include papilledema, orthoptic outcomes; forehead shape; cognitive, behavioural and psychological outcomes; and societal costs. A cost-effectiveness analysis will be performed.Ethics and dissemination The study has been reviewed and approved by the Medical Research Ethics Committee of the Erasmus MC, University Medical Center Rotterdam (MEC-2022-0142). Written informed consent will be obtained from both parents of each participant. The results will be disseminated by publication in international peer-reviewed journals.Trial registration number ClinicalTrials.gov NCT06069479.